Kesaksian Testimonium De Auditu dalam Upaya Pembuktian Tindak Pidana Persetubuhan dalam Perspektif Hukum Progresif - Nanis, Volkes (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research more focuses on the value of testimony witness testimonium de auditu in the case of coitus that the only one witness only while in the training kuhap we know one witness not witness. But the problems studied is how the value of testimony testimonium de auditu for evidence of the criminal intercourse? How can the application of testimony testimonium de auditu in an effort to of coitus according to criminal law progressive perspective?.The research is legal research normative with pendakatan case, approach perundang-undangan and approach concept. The results of the study found that the value of testimony testimonium de auditu but did not have the decisions dropped by a judge is a form of a breakthrough law as he will by law progressive therefore suggested should be in a criminal offense coitus testimony from testimonum de auditu in admit and needs to get a rule khsusus about crime coitus with the utmost one witness is a witness.